Drag reduction and heat transfer enhancement of water flow in a channel - Pak, Kai Xun (Nanyang Technological University, 2024)
Frictional losses encountered by a flowing fluid due to opposing acting drag forces or fluid resistance while transporting large amounts of fluid over long distances have been a concern for most flow systems. In addition to the fouling accumulation, it has resulted in a significant increase in pumping power required to overcome these factors. Thus, many researchers have explored potential Drag Reducing (DR) agents that could potentially mitigate such losses. However, drag reduction comes at the expense of compromising the fluid’s heat transfer capabilities which is a critical aspect for district cooling applications when transporting chilled water for the heat exchange process at the point of use. This project aims to review the existing literature on research performed by previous researchers to achieve similar results and to make further investigations into the drag reduction and heat transfer enhancement process. The deliverables of this project also include the improvement of the accuracy and reliability of the test rig. The existing test section has been reviewed by the author to single out underlying issues and possible design improvements to achieve better results. This study uses a test facility where experiments are conducted and data such as pressure drop, temperature, and volumetric flow rate are measured and tabulated for further analysis of this phenomenon. The report is also inclusive of a new design for the test rig which allows for increased versatility in manipulation and experimentation possibilities. The capabilities of the newly designed rig allow for analysis of the effectiveness of the formation of Shear Induced Structure (SIS), trialling different insertions to exert shear stress over the surfactant’s limits to remove its DR ability and regain heat transfer capabilities. Lastly, studies on the rate of recovery for ionic surfactants which has the ability to self-repair can also be performed on the newly designed experimental rig. III The classification of DR agents comprises of two main categories, namely Polymer Additives and Surfactant additives. This experiment utilises a cationic additive within the subgroup of Surfactant additives, Cetyltrimethylammonium (CTAC) and Sodium Salicylate (NaSal) at varying Parts Per Million (ppm) concentrations namely 30,60 and 90ppm. This study is designed to investigate the DR properties and heat transfer capabilities associated with these selected additives within the specific subgroups.